A study on nutritional status of children of under five years in chhaimale VDC, Kathmandu. - Pokharel, Tanka Maya (2009)
ABSTRACT: The main objective of this study entitled "Nutritional status of under five years children in Chhaimale VDC Kathmandu" was to find out the nutrition status of children in the study area. This study has been prepared for the partial fulfillment of the requirements for the master's degree in Education (Health Education) Chhaimale VDC, near the capital town was selected for the study. There were 5125 people in 825 household all over the V.D.C. Among the 360 children under five years only 120 children and their mothers were selected for sampling from ward no. 1,3,5 and 7. Among 120 selected children 68 were boys and 52 were girls. Purposive sampling method was used as sampling. The researcher used questionnaire observation forms, weighting machine, measurement tape and MUAC tape as a research tools. In this study 42.5 percent mothers were illiterate among them 44.16 percent were involved in household work, only 6.66 percent were involved in business and 56.66 percent were involved in agriculture. The soci-cultural status was as rural people of different Nepalese society. The nutritional status of children was low in indicator but height and weight of most children was normally. Regular long term breast feeding practice was not sufficient to the child in the study area. personal hygiene and food hygiene was not satisfactory in the study area. Most of the children's nutritional status was good whose mothers were educated. Traditional food practices were not sufficient for children. The study has suggested that the urgent needed of nutrition health education and personal hygiene in rural area. The study has stopped that the further researcher could find out the better nutritional status of all children.